Наукові записки кафедри педагогіки. Вип. 38 - (:unkn) unknown (Харків : Харківський національний університет імені В. Н. Каразіна, 2015)
До збірника включено статті, які об’єднує тема виховання як засобу досягнення гармонії і злагоди особистості з довкіллям. Дослідження спираються на культурологічну ідею, що означає розкриття закономірностей освіти через аналіз впливу різних видів культури, мистецтва, мови на вдосконалення морально-духовного розвитку особистості, зміцнення здоров’я та забезпечення активного довголіття через постійний пошук умов злагоди, гармонії студентів, учнів, співробітників на засадах співробітництва. Соціальна ідея та особистісна культура розглядаються з погляду підготовки вихованця до адекватного вибору поведінки та успішної діяльності. Для науковців, аспірантів, викладачів вищих навчальних закладів, студентів, вчителів.
Keywords: SOCIAL SCIENCES::Social sciences::Education; SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology; andragogy; affined work; aesthetic education students; aesthetic education; adult learning; Bologna process; bioadequate method; artistic upbringing; artistic and aesthetic taste; art; competence; compendium; cognitive interest; civil position; children with special needs; creative thinking; creative activities; cooperation strategy; conciliation; competency; education; design-training technologies of learning; culture dialogue; culture; cultural and historical heritage; educational work; educational system; educational process; educational environment; education quality; humanitarian environment; French language; family section of the national-patriotic education students; gender education; gender culture; inclusion; improving the efficiency of learning; image; humanization; humanitarization; innovative behavior of students; independent work of a student; increasing the level of cognitive interest; inclusive environment; inclusive education; language culture; language; international innovative experience in the sphere of education; interactive technologies; interactive learning technologies; lexicographic culture; lexicographic competence; lecturer; lecture; learning achievements; moral education; microcosm; means of professional training; Master’s degree program; macrocosm; national consciousness; motive; motivation; multimedia technologies; morally-spiritual culture; obrazon; nonpedagogical fields; new educational technology; national-patriotic education; national section of the national-patriotic education students; pedagogical technologies; paradigm; patriotism; pedagogical competency; pedagogical ethics; positive self-concept; personnel; personal culture; positive parenting; positive motivation forming; reading; psychologist-consultant; professional pedagogical training; professional competence; problem-solving method; self-education students; self-concept; scientific and methodic work; role play; reading cultur; Skovoroda Grigoriy Savich (1722-1794); simultaneous function of the eye; self-knowledge; self-evaluation of learning achievements; self-efficacy; student; spiritual development of the personality; special needs